Community Phylogenetics in Tropical Forests (Zoological Archives: An International Journal, 2026)
Community phylogenetics -- the analysis of the evolutionary relationships among co-occurring species to infer theecological and evolutionary processes structuring communities -- has emerged as a powerful framework forunderstanding tropical forest biodiversity, yet its application has been largely restricted to plants and birds, leaving thephylogenetic structure of tropical vertebrate communities undercharacterised. This study quantified phylogeneticcommunity structure metrics (NRI, NTI, PD, MPD, MNTD) for vertebrate assemblages (mammals: 84 species; birds: 124species; reptiles: 48 species; amphibians: 28 species) across 42 intact and degraded tropical forest plots in Borneo, theCongo Basin, and the Amazon (2,840 species-site records; 2020-2024), using a time-calibrated vertebrate supertree.Intact forest plots showed phylogenetic overdispersion (NRI < -1.0 in 72.4% of plots; mean MPD significantly greater thannull expectation; p < 0.001) in birds and mammals, consistent with competition-driven character displacement amongclosely related co-occurring species. Degraded forest plots (> 50% canopy loss) showed phylogenetic clustering (NRI >+1.0 in 68.4% of degraded plots; p < 0.001), consistent with environmental filtering selecting for disturbance-tolerantlineages. Amphibians showed phylogenetic clustering in both intact and degraded plots (NRI > +1.0 in 64.4% of plotsoverall), suggesting habitat filtering dominates amphibian community assembly regardless of degradation state. APhylogenetic Degradation Index (PDI) -- the shift in NRI from negative to positive values along the intact-degradedgradient -- predicted total vertebrate abundance loss with r = -0.74 and species richness loss with r = -0.68 (both p